AN EXPERIMENTAL STUDY ON BIASED COGNITIVE PROCESSING IN ACCIDENTALLY INJURED PATIENTS WITH DIFFERENT POSTTRAUMATIC GROWTH LEVELS - liang, zhenhong; Liu, XiaoHong; Gong, ShuMei (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Various studies have assessed the negative and/or positive changes in the aftermath of traumatic events. Accidental injuries (such as accidents, injuries, etc.), for its high incidence and disability rate, is easy to cause serious psychological problems and hinder the physical and psychological rehabilitation of the patients. Material and Methods: To explore the characteristics of attention bias in accidentally injured patients with different levels of Posttraumatic growth (PTG), total score of PTG was adopted to screen out 15 high-PTG group and low-PTG group respectively among accidentally injured patients. Dot probe task was used with positive, negative and neutral facial expression pictures as experimental materials. An experimental design of 2 (facial expression: positive and negative)×2 (consistency of probe point and facial expression: consistent and inconsistent)×2 (PTG level: high and low) was employed. Results: Patients with low PTG level had attention bias toward the negative emotional stimuli, and difficulty in distraction from the negative emotional pictures. The value of D and DI were both significantly greater than 0 (p<0.05). Patients with high PTG level did not demonstrate significant attention bias toward positive or negative emotional stimuli. The responding time of patients with high PTG level was significantly shorter than that in patients with low PTG level in the incongruent task (p<0.05). Conclusion: There are different characteristics of implicit cognitive processing in patients with different level of PTG, suggesting the necessity of psychological intervention on the accidentally injured patients.